Price transmission in selected Malaysian fruits markets - Mohamed Arshad, Fatimah; Abdel Hameed, Amna Awad (Science Publications, 2014)
The market for fresh produce such as fruits in Malaysia is alleged to be inefficient due to poor flow of information between market levels and uncompetitive market particularly at the wholesale and retail levels. Due to these structural problems, pricing efficiency is questionable, in that they are not integrated. This study intends to examine the cointegration and causality relationships between the farm and retail prices in the Malaysian market of fruits. To that end, the bivariate cointegration approach, using Granger causality tests, is applied. The study uses monthly data from January 2000 through December 2010. The results show that there is evidence of long run bidirectional causal relationship between farm and retail prices for banana and watermelon. However, the analysis revealed a long run unidirectional relationship from farm prices to retail prices with no evidence of reverse or feedback causality running from farm price to retail prices for jackfruit and durian.